Knowledge Management in Mergers and Acquisitions: key factors - Orsi, Ademar (Review of Business Management, 2007)
The linking between competitiveness and knowledge has been object of increasing attention and subject of discussion in the enterprise and academic field. The evaluation of the existing knowledge and the comparison with the future necessities consist in the strategically management of the knowledge. Literature points at two routes for institutions to obtain the knowledge they lack: internal development and incorporation of external bases. Some enterprises choose to incorporate external bases of knowledge through the acquisition of other firms that have already undergone the learning process and which are acknowledged in the market. However, this apparently hasty solution hides problems that are inherent to the change management in merges and acquisitions, mostly in cultural aspects. A contribution of this study includes the identification and discussion of the critical factors of these processes. Key-words: Knowledge management. Organizational change. Organizational culture.